End of days - Alten, Steve (Grim reaper, 2010)
Patrick "Shep" Shepherd was a promising major league baseball pitcher before September 11th, 2001. Shaken by the terrorist attacks, Shep left behind his wife and newborn daughter to enlist in the Armed Forces. Eleven years later, Shep finds himself in Manhattan's VA hospital. His left arm is gone, his wife and daughter are gone, and his tarnished soul is haunted by the nightmares of war. Mary Klipot, a scientist working at a biohazard level-4 lab in Fort Detrick, enters Manhattan with Scythe, a swift-acting version of the Black Death. Believing she was chosen to bring forth the End of Days she infects herself, unleashing a pandemic. Shep is the only one with the vaccine which he is determined to use to save his wife and child.